Characteristics and Outcome of Arthroscopic Femoroacetabular Impingement Surgery in the National Football League. Issue 7 (21st July 2017) - Nwachukwu, Benedict U.; Premkumar, Ajay; Fader, Ryan; Bedi, Asheesh; Kelly, Bryan T.
Objectives: There is an increased understanding of hip injury and femoroacetabular impingement (FAI) in elite athlete. Previous evidence suggests that hip pathology accounts for 10% of injuries in football players. The impact of FAI and arthroscopic FAI surgery has not been previously studied for National Football League (NFL) players. The purpose of this study was to investigate the impact of arthroscopic FAI surgery on return to play (RTP) and RTP performance in NFL players. Methods: NFL players undergoing arthroscopic FAI surgery between 2006 and 2014 by two surgeons were identified. Medical records were reviewed for demographic, clinical and operative variables. RTP and RTP performance was assessed based on a review of publically available NFL player statistics. RTP and RTP performance data included time to return to play, games played pre and post season of injury, yearly total yards and touchdowns for offensive players, and yearly total tackles, sacks, and interceptions for defensive players. Offensive power ratings (OPR = [total yards/10] + [total touchdowns × 6]) and defensive power ratings (DPR = total tackles + [total sacks × 2] + [total interceptions × 2]) were calculated for the pre-injury season and the post injury season. Paired t-tests comparing pre and post injury seasons were performed. Results: Forty-eight hips in 40 NFL players were included; eight players underwent bilateral hip arthroscopies. Included players underwent surgery at mean 25.6 years (SD+ 4.6) and had a mean body mass index of 31.3 (SD+ 4.6). The majority of players were offensive (N=24; 60%) with the offensive line (N=11; 27.5%) being the most common of all positions. Of the 48 included hips, all had labral tears and 41 (85.4%) underwent labral repair while the remainder had a debridement. Forty-two of the 48 hips (87.5%) underwent CAM decompression, 28 (58.3%) received Subspine decompression and ten (20.8%) underwent rim decompression. The capsule was repaired in 35 of the 48 (72.9%) hip surgeries. Of the 40 included players, 37 (92.5%) achieved RTP after their arthroscopic hip surgeries at mean of 6.0 months. Prior to injury, included patients played in a mean of 11.0 games compared to 9.5 games in their post surgery season (p=0.26). Mean offensive and defensive power ratings (OPR, DPR) demonstrated a non-significant decline in the post surgical season (OPR Pre-injury 40.2, OPR Post-Injury 32.3; p=0.34) (DPR Pre-Injury 49.6, DPR Post-Injury 36.4; p=0.10). There was no significant difference in mean annual salaries based on contracts negotiated pre-injury and the first negotiated contract after surgery (Pre-Injury: $3.3M; Post-Injury: $3.6M; p=0.58) Conclusion: There is a very high rate (92.5%) of return to play in the NFL after arthroscopic FAI surgery; this rate is higher than what has been previously reported for other orthopaedic procedures. Additionally, NFL players are able to achieve a return to sport at a faster time frame (6 months) than previously reported for other procedures. There does appear to be a non-significant decline in both offensive and defensive performance with defensive performance experiencing a greater magnitude of decline. It is unclear whether the decreased on-field statistics are attributable to the surgical procedure or an expected age related decline in performance. Undergoing surgery does not appear to have a financial impact however. These findings have important implications for counseling elite athletes about the expected impact of arthroscopic FAI surgery.